Material didáctico innovador para la construcción de aprendizajes significativos durante el proceso áulico de la asignatura de Biología. Periodo lectivo 2022 – 2023. - Astudillo Ambuludí, Marcos Javier (2024)
The implementation of the innovative didactic material promotes the interest, curiosity and active participation of the students in the classroom process, strengthening it and facilitating the students' understanding of the theoretical contents and, in turn, contributing to the construction of significant learning. The objective of this Curricular Integration Work was to promote the construction of significant learning in students, through the implementation of innovative didactic material, in the classroom process of the Biology subject, of the 2nd year Baccalaureate, of the Educative Unit "Daniel Álvarez Burneo", during the academic year 2022 - 2023. For the present research work, the inductive method was used; since, through direct observation, the problem was identified and, later, through bibliographic information, the intervention proposal was elaborated and developed, with the purpose of solving the problem. The research has a qualitative approach, which allowed to identify strengths and weaknesses of the educational environment, regarding the implementation of innovative didactic material for the construction of significant learning in students. In addition, according to the nature of the information, it is action-participatory research, because the inclusion and interaction of the students and the researcher was encouraged to generate solutions to the identified problem. According to the temporality, it is transversal; since, from the diagnosis to the discussion of results, it corresponds to a short period of time. The results obtained through the research instruments denoted that the implementation of innovative didactic material, such as: mini-atlas, brochures, slides, virtual infographics, images printed on photographic paper and informative sheets, facilitated the understanding of the information and improved the student learning experience. It is concluded that the innovative didactic material implemented in the classroom process of the Biology subject promotes the construction of significant learning in students. Key words: Teaching-learning process, student interest, academic curiosity, active participation.